1975
DOI: 10.1002/pen.760150207
|View full text |Cite
|
Sign up to set email alerts
|

Ultra‐high molecular weight high‐density polyethylene as a gear material

Abstract: Tests have been made for use of a high‐density polyethylene of ultra‐high molecular weight as a gear material. The gears had a diametral pitch of 10 and 30 teeth. They were tested in mesh with a steel gear of the same size in two operating conditions: (1) in still air without lubrication, and (2) in oil with generous lubrication.The effects of speed, temperature, and initial lubrication on the load capacity of the gears were tested and an equation was developed to express the limits of these gears operating wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1981
1981
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…The driving gearwheel and the driven gearwheel in the test gearbox are connected to the corresponding gearwheels under test, made of polymer material, through four universal couplings (5). A notable feature of this test bench is the procedure by which the constant torque is maintained for the gearwheels under test (9). The test gearbox is allowed to rotate by hinging it on an independent block, preventing gear wear from affecting the supplied torque.…”
Section: Basic Test Bench Designmentioning
confidence: 99%
See 2 more Smart Citations
“…The driving gearwheel and the driven gearwheel in the test gearbox are connected to the corresponding gearwheels under test, made of polymer material, through four universal couplings (5). A notable feature of this test bench is the procedure by which the constant torque is maintained for the gearwheels under test (9). The test gearbox is allowed to rotate by hinging it on an independent block, preventing gear wear from affecting the supplied torque.…”
Section: Basic Test Bench Designmentioning
confidence: 99%
“…By observing the balance of moments concerning the shaft pivot (10), the constant torque provided by the weight (7) applied to the test wheels is counterbalanced by the twisting moments acting on the shafts (9). It can be noted that the two torques T 1 and T 2 have opposite directions to the moment due to the weight.…”
Section: Analysis Of the Load Applied To The Test Wheelsmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Figure 6, glass fiber, cement and carbon nano tube reinforcement have been investigated with PP to improve their thermal and mechanical properties for gear applications. Yelle and Poupard 56 checked the usefulness of ultra-high molecular weight high-density polyethylene (UHMW/HDPE) for gear material for power transmission systems. ABS and HDPE along with acetal gears have been studied and compared for their performance evaluation by Singh and Singh.…”
Section: Classification Of Review Of Polymer Gearingmentioning
confidence: 99%
“…It has excellent sound absorbing feature and show resistance to fatigue and impact. Yelle and Poupard 3 showed that the ultra-high molecular weight high-density polyethylene (UHMW/HDPE) can be used to fabricate gears for power transmission. Although, it is a very expensive material 4 it has good mechanical properties combined with high chemical and abrasion resistance.…”
Section: Materials Of Interest For Polymer Gearsmentioning
confidence: 99%